Padalang tinig - Castillo, Nicole Ann; Lejano, Eduard, Jr. J. (Quezon City, Philippines College of Mass Communication, University of the Philippines Diliman, 2009)
The film is about the sacrifice of an eldest daughter in order to fulfill her responsibilities to her family. Lourdes sacrificed her own goals in order to take care and send her younger sister, Lima to school.
Now Lourdes feels upset. Upset, because she feels that she cannot carry out her goals anymore. She feels that she cannot get out of that cycle of responsibilities vested on her. Because Lima decided to support her child, Margaret by living the country, while leaving her daughter with Lourdes.

Lourdes accepted the responsibility of taking care of Margaret; but she is very aloof and strict with the child. But despite the strictness, Margaret felt it as "love".

On the other hand, Lima didn't forget to send her ate voice tapes and PX goods for her small business. However, Lourdes didn't answer any of her voice tapes. Towards the end of the story, Lourdes would start to realize through the child how important and loved she is. In the end, Lourdes would decide to record a voice tape to Lima. This would be the start of her acceptance of the situation she is in.
Thesis (BA Film and Audiovisual Communication)
Keywords: Short films -- Philippines; Family -- Philippines; Women -- Philippines; Padalang tinig (Short film)